Injections of botulinum toxin A into the salivary glands improve sialorrhoea in amyotrophic lateral sclerosis. Issue 1 (1st July 2000) - Giess, R; Naumann, M; Werner, E; Riemann, R; Beck, M; Puls, I; Reiners, C; Toyka, K V
Abstract : Sialorrhoea is a socially disabling problem in bulbar amyotrophic lateral sclerosis (ALS). Botulinum toxin A (BoNT/A) was injected into the salivary glands in five patients with bulbar ALS and sialorrhoea. The effect of BoNT/A was measured by the number of paper handkerchiefs used each day and by salivary gland scintigraphy. BoNT/A ameliorated sialorrhoea and quality of life without major adverse effects. BoNT/A may be a relatively safe and effective treatment for sialorrhoea in selected patients.